Liability of corporate groups : autonomy and control in parent-subsidiary relationships in US, German and EU law. An international and comparative perspective /: autonomy and control in parent-subsidiary relationships in US, German and EU law. An international and comparative perspective. (1980) - Antunes, José Engrácia
No abstract available